2013
DOI: 10.1094/mpmi-12-12-0301-r
|View full text |Cite
|
Sign up to set email alerts
|

Nicotiana benthamiana Calreticulin 3a Is Required for the Ethylene-Mediated Production of Phytoalexins and Disease Resistance Against Oomycete Pathogen Phytophthora infestans

Abstract: Mature Nicotiana benthamiana shows strong resistance to the potato late blight pathogen Phytophthora infestans. By screening using virus-induced random gene silencing, we isolated a gene for plant-specific calreticulin NbCRT3a as a required gene for resistance of N. benthamiana against P. infestans. NbCRT3a encodes an endoplasmic reticulum quality-control (ERQC) chaperone for the maturation of glycoproteins, including glycosylated cell-surface receptors. NbCRT3a-silenced plants showed no detectable growth defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 57 publications
0
44
0
Order By: Relevance
“…Five silencing constructs (A1-190, A2-117, A2-158, A2-189, and A6-96) causing a significant reduction in resistance against P. infestans were found to encode full-size ABCG (PDR-type) transporters ( Figure 2B, Table 1). Further analyses of other lines not listed in Table 1 have been reported (Matsukawa et al, 2013;Ohtsu et al, 2014) or are in progress and will be reported elsewhere.…”
Section: Identification Of N Benthamiana Genes Required For Resistanmentioning
confidence: 99%
See 4 more Smart Citations
“…Five silencing constructs (A1-190, A2-117, A2-158, A2-189, and A6-96) causing a significant reduction in resistance against P. infestans were found to encode full-size ABCG (PDR-type) transporters ( Figure 2B, Table 1). Further analyses of other lines not listed in Table 1 have been reported (Matsukawa et al, 2013;Ohtsu et al, 2014) or are in progress and will be reported elsewhere.…”
Section: Identification Of N Benthamiana Genes Required For Resistanmentioning
confidence: 99%
“…Given that N. benthamiana has an allopolyploid genome (Goodin et al, 2008), the two copies of Nb-ABCG1 were presumably derived from the Nicotiana species ancestral to N. benthamiana. In fact, we often find two copies of highly homologous genes in the genome sequence of N. benthamiana (Table 1; Matsukawa et al, 2013;Ohtsu et al, 2014). Because the nucleic acid sequences of the two Nb-ABCG1 genes were highly similar, we could not suppress expression of a single Nb-ABCG1 gene.…”
Section: Identification Of N Benthamiana Genes Required For Resistanmentioning
confidence: 99%
See 3 more Smart Citations